A Literature Study: Relationship between the Translation Competency and Translation Quality - Ariyanti, Meidya Laksmi; Tanjung, Sufriati (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
Translation competency consists ofknowledge and skills acquired by translators to produce agood quality translation. Translation competency includesformal education and / or translation trainings whichtranslators have ever taken. Even so, many translators inIndonesia do not have backgrounds of acquiring formaleducation and / or attending translation trainings. In thisregard, this literature study was conducted to investigateregarding the relationship between the translationcompetency and the translation quality. By examiningsome related academic researches and supported by somerelevant theories, the result shows that the translationcompetency affected the quality of translations producedby the translators